(untitled) - Mothersill, C. (Carmel) (London, 2000)
Aquatic Invertebrate Cell Culture is a very new field which has major applications in Aquaculture, Ecotoxicology and Pathology. In essence it is realised that pathogens behave differently in host cells than the impression gained from growth on agar plates. Another major application of invertebrate cell culture is an understanding of mechanisms involved in cellular and molecular responses to environmental change. This book aims to consider all relevant advances for the development of aquatic invertebrate cell culture.
Keywords: Aquatic invertebrates,Động vật thuỷ sinh; Cultures and culture media,Văn hóa và môi trường nuôi cấy